CONSTRUCCIONES Y ESPECULACIONES ENTORNO AL "DESCALABRO FINANCIERO" DEL BANCO ANGLO COSTARRICENSE - Reventós, Ciska (1995)
This article provides a preliminary sociological analysis of the crisis of the Banco Anglo Costarricense, its intervention and the decision to close the bank (June to December 1994); as a way to approach the tensions and conflicts expressed in the present period of institutional change of the financial system in Costa Rica.